A Tauberian Theorem for Double Cesàro Summability Method - Bidu Bhusan Jena; Susanta Kumar Paikray; Umakanta Misra (International Journal of Mathematics and Mathematical Sciences)
We have generalized Littlewood Tauberian theorems for (C,k,r) summability of double sequences by using oscillating behavior and de la Vallée-Poussin mean. Further, the generalization of (C,r) summability from (C,k,r) summability is given as corollaries which were earlier established by the authors.